2021
DOI: 10.31925/farmacia.2021.4.21
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Micrornas as a Diagnostic Biomarkers in the Early Prediction of Acetaminophen-Induced Liver Injury

Abstract: Toxic liver injury can vary from asymptomatic increases in biochemical parameters (hepatic function tests) to acute hepatitis and acute liver failure or death. Because this parameters changes only after the hepatocellular necrosis and changes are not proportional to the extension of the hepatic injuries, we need new biological markers to facilitate an early diagnosis, allowing a rapid and targeted therapeutical intervention. Our study aimed to analyse the changes in serum levels of some miRNAs after acetaminop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In this group, there is a significant increase in serum ALT, AST, TRIG and ALP levels (Table I) associated with a significant increase in haematological parameters such as WBC, RBC, HGB, PCT, MCHC, MPV and a significant decrease in PDW compared with the control untreated group of animals (Table II). It has been shown that hepatic steatosis is connected with high WBC and platelet counts and that higher WBC counts are a prognostic marker for the severity of hepatic steatosis, which can also be associated with chronic inflammation that can appear during disease progression [36]. In the same manner, an increase in haemoglobin in NAFLD patients correlated with the severity of steatosis [35].…”
Section: Parametersmentioning
confidence: 91%
“…In this group, there is a significant increase in serum ALT, AST, TRIG and ALP levels (Table I) associated with a significant increase in haematological parameters such as WBC, RBC, HGB, PCT, MCHC, MPV and a significant decrease in PDW compared with the control untreated group of animals (Table II). It has been shown that hepatic steatosis is connected with high WBC and platelet counts and that higher WBC counts are a prognostic marker for the severity of hepatic steatosis, which can also be associated with chronic inflammation that can appear during disease progression [36]. In the same manner, an increase in haemoglobin in NAFLD patients correlated with the severity of steatosis [35].…”
Section: Parametersmentioning
confidence: 91%
“…Other constituents were beta-phellandrene (0.029%), 3-carene (0.016%), 1,3,6octariene, 3,7-dimethyl-, (Z) (0.058%), estragole (1.09%), 2-Allyl-4-methylphenol (0.404%), 4-Butylbenzyl alcohol (0.469%), caryophyllene (0.39%), 2-ter-Butyl-4-methyl-6-(a-methylbenzyl) phenol (0.039%) and retinol acetate (0.02%) (Table V). There are several regimens for treating hepatic damage induced by synthetic drugs which produce adverse effects [13]. Hence, this study was aimed to investigate the possibility of food-derived and natural alternative for protection against chronic liver damage, a major reason for chronic liver diseases.…”
Section: Effect Of I Verum Eo On Inflammatory Markersmentioning
confidence: 99%
“…A more desired and attainable perspective would be the actual restoration of the inner state of synchrony by using gradually employed procedures, transcriptomic and environmental triggers to reset timers profoundly endorsed at the molecular level. The outcome should immediately be visible in physiologic sleep-wake cycles, with normally displayed temporal behaviour and the general health state reestablished or at least partially recuperated [37][38][39].…”
Section: Author Detailsmentioning
confidence: 99%